The Application of Total Physical Response (TPR) Method Through Songs to Improve Students' Vocabulary Mastery and Creativity: A Classroom Action Research at The First Grade - Binti, Titania; Khofifah; Fitrah Yuliawati; Raziqa; Inayah Rahmawati (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2024)
This study investigates the efficacy of using songs in conjunction with the Total Physical Response (TPR) method to enhance vocabulary mastering and creative thinking in EFL students. 36 first-grade students participated in two cycles of Classroom Action Research (CAR) at SMAN 03 Pamekasan. Students' low average score of 58 on the pre-test and initial observations indicated serious difficulties with vocabulary retention, spelling, pronunciation and accurate usage. TPR, which combines movement with language learning, was combined with songwriting exercises. In order to improve memory through dance and music, students worked in groups to compose and perform songs utilizing vocabulary words in the first cycle. Despite a 12.1% improvement in post-test scores, the results fell short of the minimal passing requirements set by English Teacher of SMAN 03 Pamekasan. Within the moment cycle, extra hone and anxiety-reducing measures, such as singing and acting out melodies some time recently testing, driven to a eminent advancement, with the normal score rising to 80. The think about found that the TPR strategy, when combined with tunes, altogether improved students' lexicon run, spelling, articulation, and exactness of utilization. Additionally, it cultivated more prominent understudy engagement, motivation, and inventiveness within the classroom. By and large, the investigate illustrates that TPR and tunes offer an compelling, intuitively approach to lexicon learning, making a difference understudies overcome challenges in dialect securing and making a more energetic and agreeable learning environment.